Knowledge motives in the cross-border acquisitions: a case research of three Brazilian multinationals - Mazon, Gisele (2021)
Purpose – This qualitative study, which is based on multiple cases, aims to analyze the pattern of acquisitions by Brazilian multinationals, such as Gerdau in the steel industry, Petrobrás in the oil and gas industry and Vale in the mining industry, to infer the likely knowledge motivations underlying the acquisitions of these firms. Design/methodology/approach – The analyses of the three cases, with secondary data collected for the period from 2003 to 2007, classify the acquisitions according to the extent of the exploration or exploitation of resources and in two dimensions: business knowledge and location knowledge, in accordance with Ferreira’s (2005) model based on March (1991) and Chandler (1962). Findings – The findings showed that the acquisitions by Gerdau, Petrobrás and Vale favored the exploitation of their resources and capabilities developed in the home market more than the exploration of new resources and capabilities. Regarding the ownership acquired, this study failed to observe the likely expected pattern of acquiring a majority stake for sustaining an exploitation strategy or a minority stake for sustaining an exploration strategy. Originality/value – This study makes three contributions. First, the need to analyze the potential gains of new knowledge acquisition in domestic and cross-border expansion. Second, considering the opportunity to explore new resources and knowledge even for firms in commodity industries. Third, considering how the equity held is a structural solution that needs to be adjusted to the knowledge strategy.